Trends and current spectrum of contact allergy in Central Europe: results of the Information Network of Departments of Dermatology (IVDK) 2007–2018 - Uter, Wolfgang; Gefeller, Olaf; Mahler, Vera; Geier, J. (British Journal of Dermatology, 2020)
Background: Changing patterns of exposure lead to changes in the spectrum of contact allergy in the general population and in patients patch tested for suspected contact allergy. The main contact allergens (haptens) are assembled in the so-called ‘baseline series’. Objectives: To present the current spectrum of contact allergy to baseline series allergens, and its temporal development over the last 12 years, based on data collected by the 56 active departments of the trinational Information Network of Departments of Dermatology (IVDK). Methods: Patch-test data, along with core demographic and clinical information, subdivided into 4-year periods for all patients patch tested with the baseline series in the IVDK, were analysed descriptively. Moreover, log-binomial regression analysis addressed temporal trends of specific contact allergies, adjusted for potentially confounding factors. Results: Among the 125 436 patients tested with the German baseline series, the most common allergens were nickel (14·7%), fragrance mix I (8·1%), Myroxylon pereirae resin (7·5%) and cobalt (5·2%), with no conclusive trend. The rise and fall of contact allergy to methylchloroisothiazolinone/methylisothiazolinone (MI), following (self-) regulation in the European Union, reflected the MI contact allergy epidemic. Propolis showed a marked upward trend with a prevalence of 3·94% during the period 2015–2018. Conclusions: Decreases in sensitization prevalence likely reflect reduced exposure, with some lag, as seen with hydroxyisohexyl 3-cyclohexene carboxaldehyde. If no (sufficient) decrease can be observed despite interventions, such as for nickel and chromium, affected subgroups should be identified and their causative exposures explored. Finally, increases such as that observed with propolis, certainly warrant targeted investigation of the exposures driving sensitization, and possibly intervention.
CRIS-Team Scopus Importer:2020-04-07